Clinical Outcome of Children With Suspected Shunt Malfunction Evaluated in the Emergency Department. Issue 6 (16th March 2015) - Sribnick, Eric; Sarda, Samir; Moore, Mike; Capasse, Meredith; Tubbs, R. Shane; Wrubel, David; Chern, Joshua J.
Abstract: BACKGROUND: Patients with cerebrospinal fluid shunts frequently present to the emergency department (ED) with suspected shunt malfunction. The outcome of those patients who were discharged from ED when shunt malfunction was deemed unlikely has not been previously documented. OBJECTIVE: To demonstrate there is no increase in severity or likelihood of harm for patients who are discharged directly from the ED after adequate evaluation, as compared to patients who were selected for inpatient hospitalization. METHODS: The report screens 3080 ED visits between 2010 and 2013 made by patients with shunted hydrocephalus. ED visits preceded by another ED visit or neurosurgical procedures within 60 days were excluded. ED visits for reasons unrelated to shunt function were excluded, and 1943 visits met the inclusion criteria. Final dispositions from the ED included home (n = 1176), admission to neurosurgery service (n = 550), and admission to other services (n = 217). Subsequent events within 30 days, including ED visits and elective and nonelective shunt-related surgery, were reviewed. RESULTS: The clinical characteristics of the 3 groups were similar. Of patients discharged home from the ED, 19.0% returned to ED, and 4.5% required shunt-related surgeries. Of the patients admitted for observation, 18.7% returned to ED and 14.2% required shunt-related surgery. Of the patients admitted to other hospital services, 19.6% patients returned to the ED, with 2.0% requiring surgical intervention. There were no shunt-related mortalities in any of the 3 groups. CONCLUSION: Children with cerebrospinal fluid shunts are often evaluated in the ED. Discharge from the ED, when suspicion for shunt malfunction is low, is an appropriate practice.